2007
DOI: 10.1105/tpc.106.048058
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of Cellulose Synthases Required forArabidopsisSecondary Cell Wall Formation Enhances Disease Resistance

Abstract: Cellulose is synthesized by cellulose synthases (CESAs) contained in plasma membrane-localized complexes. In Arabidopsis thaliana, three types of CESA subunits (CESA4/IRREGULAR XYLEM5 [IRX5], CESA7/IRX3, and CESA8/IRX1) are required for secondary cell wall formation. We report that mutations in these proteins conferred enhanced resistance to the soil-borne bacterium Ralstonia solanacearum and the necrotrophic fungus Plectosphaerella cucumerina. By contrast, susceptibility to these pathogens was not altered in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
402
1
30

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 410 publications
(459 citation statements)
references
References 87 publications
26
402
1
30
Order By: Relevance
“…The fact that coi1 has enhanced susceptibility to most foliar necrotrophic fungi (Thomma et al, 1998;Lorenzo et al, 2004;Guo and Stotz, 2007;Hernandez-Blanco et al, 2007), but increased resistance to F. oxysporum, suggests that other root-infecting fungi might actively use the JA signaling pathway to promote disease. However, coi1 also displays enhanced susceptibility to the soil-borne oomycete pathogens Pythium irregulare (Adie et al, 2007) and Pythium mastophorum (Vijayan et al, 1998), as well as the vascular wilt-inciting fungal pathogen Verticillium longispo- rum (Johansson et al, 2006), suggesting that the effect of the coi1 mutation in restricting disease symptom development is more specific to F. oxysporum.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that coi1 has enhanced susceptibility to most foliar necrotrophic fungi (Thomma et al, 1998;Lorenzo et al, 2004;Guo and Stotz, 2007;Hernandez-Blanco et al, 2007), but increased resistance to F. oxysporum, suggests that other root-infecting fungi might actively use the JA signaling pathway to promote disease. However, coi1 also displays enhanced susceptibility to the soil-borne oomycete pathogens Pythium irregulare (Adie et al, 2007) and Pythium mastophorum (Vijayan et al, 1998), as well as the vascular wilt-inciting fungal pathogen Verticillium longispo- rum (Johansson et al, 2006), suggesting that the effect of the coi1 mutation in restricting disease symptom development is more specific to F. oxysporum.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the ABA biosynthesis pathway is also required for the full virulence of the obligate oomycete pathogen H. arabidopsis in terms of asexual spore production and proliferating hyphal growth, while ABA positively regulates resistance against necrotrophic A. brassicicola infection, indicating strikingly different roles of ABA in the interactions with bio/hemibiotrophs and necrotrophs. However, contradictory roles of ABA in other pathosystems have also been documented; for example, ABA suppresses resistance to necrotrophic pathogens, including Botrytis cinerea, Fusarium oxysporum, Plectosphaerella cucumerina, and Erwinia chrysanthemi (Audenaert et al, 2002;Anderson et al, 2004;Hernandez-Blanco et al, 2007;Asselbergh et al, 2008b), and ABA signaling may positively regulate the RLM1 Col determined resistance to the hemibiotrophic fungal pathogen Leptosphaeria maculans and the edr1-mediated resistance to the obligate biotrophic powdery mildew pathogen Golovinomyces cichoracearum in Arabidopsis (Kaliff, et al, 2007;Wawrzynska et al, 2008). Hence, specific manifestations of the emerging new role for the abiotic stress signal ABA in modulating disease resistance may depend not only on pathogen lifestyle and overall infection biology but also on specialized features of each interaction, indicating that complex nuanced mechanisms underlie ABA modulation of plant biotic stresses.…”
Section: Discussionmentioning
confidence: 99%
“…This accords with the observation that flg22 peptide induced basal resistance, which is largely independent of SA, JA, or ET signaling pathways in suppressing growth of virulent bacteria (Zipfel et al, 2004;Tsuda et al, 2008), was also suppressed in the cds2-1D mutant. Likewise, the enhanced resistance to the soil-borne bacterium Ralstonia solanacearum in Arabidopsis mutants compromised in secondary cell wall formation is not dependent on SA, JA, or ET but closely associated with ABA biosynthesis and signaling pathways (Hernandez-Blanco et al, 2007). Recent findings that ABA acts as a proinflammatory cytokine in granulocytes (Bruzzone et al, 2007), which requires cADP-Rib as second messenger, is a reminiscent of some aspects of ABA signaling in the plant response to abiotic stresses (Wu et al, 1997;Sanchez et al, 2004).…”
Section: Aba Modulation Of Plant Disease Resistance Mechanismsmentioning
confidence: 99%
“…Recent studies demonstrated the importance of the cell wall in immune responses against diverse pathogens [61][62][63][64][65]. Thickness or reinforcement of the cell wall plays important roles in counteracting the penetration of fungal pathogens [66,67].…”
Section: Discussionmentioning
confidence: 99%